Microwave Acoustic Devices: Recent Advances and Outlook - Gong, Songbin; Lu, Ruochen; Yang, Yansong; Gao, Liuqing; Hassanien, Ahmed E. (IEEE journal of microwaves, 2021)
This paper presents a short review of the microwave acoustics area, where exciting material innovations and performance advancements have been made in the past decade. The ever-growing demand for more sophisticated passive signal processing functions on-chip has fueled these developments. As a result, microwave acoustic devices have maintained performance leadership in mobile applications. By evaluating three fundamental parameters, namely electromechanical coupling (k 2 ), quality factors, and frequency scalability, of microwave acoustics, this paper aims to, extensively but not exhaustively, capture the rationales behind approaches achieving higher performance microsystems. Outlooks for different material systems and addressing their underlying challenges are also offered in hopes of establishing a balanced roadmap for future microwave acoustics development.